The determination of flow characteristics in pump sump physical model - ., Nur F.I.R; ., Siti H.A.T; ., Norsyazliana S.S.A; ., Syarifah I.N.S.H; ., Muhammad S.A. (Penerbit UTHM, 2020)
Pump sump is one of the elements used in the field of hydraulic engineering where it functions as a tool that drives water. However, things that can interfere with the performance of water reservoir pumps are uneven water flows that can cause turbulence in the water pump sump, vibrations and unwanted noise. Hence, the tests were performed in a scaled physical model to determine the flow characteristics and velocity distribution in the pump sump. Two types of water level were tested at the normal water level of 0.45 m and the minimum water level at 0.25 m. Tests were carried out for twelve cases for both water levels with different flow rates 11 L/s, 9 L/s, 8 L/s, 6 L/s, 4 L/s and 1 L/s. The experiment was conducted at the Water Resources Laboratory, Universiti Tun Hussein Onn Malaysia. Hence, the dye injection technique was used in this study just to identify the distribution. The results showed that the flow of water frequently changed as it has a variety of flow rates and also according to the velocity distribution. Therefore, the velocity distribution was higher in the middle zone of the pump sump due to high pressure. The velocity distribution at the end of the section also changed probably due to the suction effect of the pump operation. The mechanism of submerged vortex occurred only at the highest of flow rates, which were under the suction pipe that caused from the bottom of the pump sump.